Whose Story Is Written on Her Dead Body? Writing Gender Justice and Transformation by Re-writing Female Victims in South African Crime Thrillers. Issue 2 (3rd July 2017) - Binder, Sabine
Abstract : Crime fiction centrally engages with questions of justice, yet often from the perspective of the detective or the criminal, thereby eliding the (conventionally female) victim. In the face of South Africa's appalling levels of gender-based violence, some crime writers are seeking new ways to write the female victim. This article asks whether the genre allows for a foregrounding of the victim's trauma and her resources. Drawing from studies on the gender dimensions of bearing witness, from postcolonial trauma theory and from scholarship on the ethics and aesthetics of representing the violated female body, it argues that the crime thrillers examined here expose and revise, yet at times also reiterate, gendered and racial assumptions about women as victims, women's suffering and the representation thereof.